Puberty and Inhibin B in 35 Adolescents With Pituitary Stalk Interruption Syndrome - Corvest, Victoria; Lemaire, Pierre; Brailly-Tabard, Sylvie; Brauner, Raja (Frontiers in Pediatrics, 2020)
Background In patients with pituitary stalk interruption syndrome (PSIS), long-term follow-up is necessary to address their gonadotrophic status. The objectives of this study were 1) to describe pubertal features of and 2) to assess the ability of serum inhibin B concentration to predict hypogonadotropic hypogonadism (HH) in patients with PSIS. Methods This retrospective single-centre study included 35 patients with PSIS and known gonadotrophic status for whom a serum sample preserved at -22°C (collected at initial evaluation or later) was available for measuring inhibin B by the same hormonal immunoassay method. Results Among the 21 boys, 15 had normal puberty (early in two), and six had partial (n=2) or complete (n=4) HH. Among the 14 girls, five had normal puberty (early in one) - four with regular menses and one in the process of puberty -, four had complete HH, and five had amenorrhea (primary in three and secondary in two) after normal pubertal development, despite a normal pubertal gonadotropin response to gonadotropin-releasing hormone test. These were considered as having partial HH. Only three boys had values over the normal lower range for serum inhibin B concentrations despite partial (n=2) or complete (n=1) HH. Inhibin B concentrations were low in all girls with complete HH, normal in all those with partial HH except in one and in those with normal puberty except in two. Considering boys and girls together, the occurrence of under-range inhibin B was significantly higher in those with HH than in those without (47% vs 10%, p= 0.02). All 15 patients with HH had associated thyroid-stimulating hormone and adrenocorticotropic hormone deficiency except for 3 girls with partial HH. Conclusions Under-range inhibin B concentrations in patients with PSIS might be suggestive of HH. These concentrations provide a simple first-line predictive test, especially in boys.